Discussion on Social Media Aesthetic War: Maurice Blanchot and the Establishment of Ethics - Šumilova, Justina (Conatus - Journal of Philosophy, 2023)
This short discussion paper proposes a non-traditional view to ethics and war, and aims to highlight new perspectives on how we view and understand war. Images, images, images are everywhere in the virtual sphere of the internet, YouTube, ads, and social media. This process of expressing oneself via the virtual image accelerates the fight for the aesthetic virtual beauty when people are trying to create an image of glorified, ideal, and perfect life. This is a mode of fight which aims to narcissistically show off their grandiosity and desire for recognition, admiration, and fascination, fighting for the viewers and followers. Such mode of hedonistic desire seems to shun ethics away from the screen. However, Maurice Blanchot, a 20th century French philosopher, who was prone to denounce the issues of his contemporary time in a rather obscure and distant way, may give us the opportunity to understand this war of aesthetics in social media and ethics.